The Effectiveness of Information and Communication Technology-Based Supervision Model Development at SMK Surakarta - Agus Maryanto; Bambang Sumardjoko; Sabar Narimo; Ahmad Muhibbin; Ma’rifah Ma’rifah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The purpose of this study is to test the feasibility of an academic supervision model based on information and communication technology. Feasibility consists of three aspects: validity, practicality, and effectiveness. This research was developed by the R&D method, which was modified into five steps, namely the define stage, design stage, development stage, and dissemination stage. The field test design is the One Group Pretest-Posttest Design. The results show that technology-based, informatics, and communication academic supervision modules with Microsoft Teams are appropriate to be applied in the implementation of technology-based academic supervision, informatics, and communication. The results obtained show that the developed model is valid, practical, and effective in increasing progress in the process of academic supervision based on technology, informatics, and communication. With this model of maximum teacher assessment, all are assessed. The assessment of academic supervision went smoothly; 126 teachers could be assessed all and more optimally. Researchers recommend that school principals implement this supervision model using Microsoft Teams. Further research is needed using different applications using models that have been developed in academic supervision assessments.